2020
DOI: 10.1002/clc.23444
|View full text |Cite
|
Sign up to set email alerts
|

The impact of chronic kidney disease on outcomes following peripheral vascular intervention

Abstract: Background: Patients with chronic kidney disease (CKD) have worsened clinical outcomes following percutaneous coronary intervention; however, limited evidence exists in patients undergoing peripheral vascular intervention (PVI). Purpose: We aimed to assess the effect of CKD on outcomes following PVI for symptomatic peripheral artery disease. Methods: Using patients from the LIBERTY 360 study, we compared the rates of 30 day and 1 year major adverse vascular events (MAVE), a composite of all-cause mortality, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As similarly shown by Yager et al in 2022 (24), advanced kidney disease was linked with noticeably increased post-nonemergent PCI mortality. Narcisse et al in 2020 (25) also showed that patients with chronic kidney disease remain at greater risk for major adverse vascular events and all-cause mortality after vascular interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As similarly shown by Yager et al in 2022 (24), advanced kidney disease was linked with noticeably increased post-nonemergent PCI mortality. Narcisse et al in 2020 (25) also showed that patients with chronic kidney disease remain at greater risk for major adverse vascular events and all-cause mortality after vascular interventions.…”
Section: Discussionmentioning
confidence: 99%